Multiple myeloma: the disease and its treatment - Gupta, Meenakshi; Pal, Rana Arun Gopal Krishan; Tikoo, Deepika (International Journal of Basic & Clinical Pharmacology, 2017)
Multiple myeloma represents a malignant proliferation of plasma cells derived from a single clone. The tumor, its products and the host response to it result in a number of organ dysfunctions and symptoms of bone pain, fracture, anemia, hypercalcemia, susceptibility to infection, neurologic symptoms, clotting abnormalities and manifestations of hyperviscosity. The cause of myeloma remains unexplained but it is associated with few occupations, inflammatory conditions, autoimmune illnesses, viral infections and genetic heterogeneity. Direct interaction between multiple myeloma cells and bone marrow cells activates pleiotropic signalling pathways that mediate growth, survival, migration of multiple myeloma cells and also resistance to chemotherapy. Although myeloma remains incurable, but the use of novel drugs like thalidomide, lenalidomide and bortezomib have resulted in a paradigm change in the therapy of myeloma. Their inclusion in current multiple myeloma treatment regimens have extended median overall survival especially in younger patient population. Recent advances in the molecular genetics have provided opportunities to design highly specific inhibitors of signal transduction pathways that may enhance the efficacy of standard chemotherapy drugs by reducing or altering the pathways associated with cell survival. Despite therapeutic advances, multiple myeloma ultimately relapses and remains an incurable disease. Current research goals are to further increase our knowledge, to identify additional targeted therapies, and to reduce adverse effects and improve response rate. This review focuses on recent clinical advancement in ant myeloma strategies with additional discussion dedicated to emerging drugs that may prove beneficial to patients with this disease.